EXHAUST GASES EMITTED BY AUTOMOBILES AND THEIR IMPACT ON THE ENVIRONMENT - O. Odilov; R. Rapiqjonov; D. A. Sheraliyev (Modern American Journals, 2025)
This article investigates the adverse effects of automobile exhaust gases on the environment, human health, and plant life. These emissions typically contain harmful substances such as carbon monoxide (CO), nitrogen oxides (NOₓ), sulphur dioxide (SO₂), and unburned hydrocarbons, which contribute significantly to air pollution and the acceleration of global warming. Prolonged exposure to these pollutants in humans can lead to chronic respiratory illnesses, cardiovascular disorders, and allergic reactions. In the plant world, toxic emissions hinder growth, reduce agricultural yields, and degrade overall ecosystem stability. The study highlights the urgent need to adopt environmentally friendly technologies and implement stringent emission controls in order to reduce vehicular pollution and safeguard public health and environmental quality.
Keywords: Exhaust gases; air pollution; global warming; vehicular emissions; chemical exposure; air quality; public health.